Proteomic signature of the Dravet syndrome in the genetic Scn1a-A1783V mouse model - Nina Miljanovic; Stefanie M. Hauck; R. Maarten van Dijk; Valentina Di Liberto; Ali Rezaei; Heidrun Potschka (Neurobiology of Disease, 2021)
Background: Dravet syndrome is a rare, severe pediatric epileptic encephalopathy associated with intellectual and motor disabilities. Proteomic profiling in a mouse model of Dravet syndrome can provide information about the molecular consequences of the genetic deficiency and about pathophysiological mechanisms developing during the disease course. Methods: A knock-in mouse model of Dravet syndrome with Scn1a haploinsufficiency was used for whole proteome, seizure, and behavioral analysis. Hippocampal tissue was dissected from two- (prior to epilepsy manifestation) and four- (following epilepsy manifestation) week-old male mice and analyzed using LC-MS/MS with label-free quantification. Proteomic data sets were subjected to bioinformatic analysis including pathway enrichment analysis. The differential expression of selected proteins was confirmed by immunohistochemical staining. Results: The findings confirmed an increased susceptibility to hyperthermia-associated seizures, the development of spontaneous seizures, and behavioral alterations in the novel Scn1a-A1873V mouse model of Dravet syndrome. As expected, proteomic analysis demonstrated more pronounced alterations following epilepsy manifestation. In particular, proteins involved in neurotransmitter dynamics, receptor and ion channel function, synaptic plasticity, astrogliosis, neoangiogenesis, and nitric oxide signaling showed a pronounced regulation in Dravet mice. Pathway enrichment analysis identified several significantly regulated pathways at the later time point, with pathways linked to synaptic transmission and glutamatergic signaling dominating the list. Conclusion: In conclusion, the whole proteome analysis in a mouse model of Dravet syndrome demonstrated complex molecular alterations in the hippocampus. Some of these alterations may have an impact on excitability or may serve a compensatory function, which, however, needs to be further confirmed by future investigations. The proteomic data indicate that, due to the molecular consequences of the genetic deficiency, the pathophysiological mechanisms may become more complex during the course of the disease. As a result, the management of Dravet syndrome may need to consider further molecular and cellular alterations. Ensuing functional follow-up studies, this data set may provide valuable guidance for the future development of novel therapeutic approaches.